Turbidites facies response to the morphological confinement of a foredeep (Cervarola Sandstones Formation, Miocene, northern Apennines, Italy). Issue 2 (25th August 2018) - Tinterri, Roberto; Piazza, Alberto
Abstract: The Cervarola Sandstones Formation, Aquitanian–Burdigalian in age, was deposited in an elongate, north‐west stretched foredeep basin formed in front of the growing northern Apennines orogenic wedge. As other Apennine foredeep deposits, such as the Marnoso‐arenacea Formation, the stratigraphic succession of the Cervarola Sandstones Formation records the progressive closure of the basin due to the propagation of thrust fronts towards the north‐east, i.e. towards the outer and shallower foreland ramp. This process produces a complex foredeep that is characterized by syn‐sedimentary structural highs and depocentres that strongly influence lateral and vertical turbidite facies distribution. This work describes and discusses this influence, providing a high‐resolution physical stratigraphy with 'bed by bed' correlations of an interval ca 1000 m thick, parallel and perpendicular to the palaeocurrents and to the main structural alignments, on an area of ca 30 km that covers the proximal portion of the Cervarola basin in the northern Apennines. The main aim is to show, for the first time ever, a detailed facies analysis of the Cervarola Sandstones Formation, based on a series of bed types that have proven fundamental to understand the morphology of the basin. The knowledge of the vertical and lateral distribution of these bed types, such as contained‐reflected and slurry (i.e. hybrid) beds, together with other important sedimentary structures, i.e. cross‐bedded bypass facies and delamination structures, is the basis for better understanding of facies processes, as well as for proposing an evolutionary model of the foredeep in relation to the syn‐sedimentary growth of the main tectonic structures. This makes the Cervarola Sandstones, like the Marnoso‐arenacea Formation, a typical example of foredeep evolution.